Speciation and Determination of Heavy Metals in Bera Lake Water by Atomic Absorption Spectrometry after Sorption on Amberlite XAD-16 Resin - Zulkafli, Nor Azreen
The concentration of some heavy metals in Bera Lake water samples collected in rainy and dry seasons has been detem1ined by atomic absorption spectroscopy. The metals in free state, bound to humic substances; and suspended particles, were fractioned according to a scheme developed. The metals were pre-concentrated on columns (1 x 10 em) packed with prepurified Amberlite XAD-16 resin. The concentrations of the metals bound to humic substances and of free metal ions were detennined after sorption-elution on the resin. The method optimized with sodium tetraborate reagent was used in detennining the free metal ions. Meanwhile, the concentrations of metal bound to suspended patticles were detennined after filtration, dissolved in concentrated nitric acid, centrifugation, and evaporation. The linearity of the detector response for the concentrations range of 0 - 2.0 ppm was excellent with a con·elation coefficient ranging between 0.998- 0.999. The recoveries ranged between 99.5- 100% with a RSD of 0.5- 1.5%. The concentration of elements found in Bera Lake water ranged: Cu (II), 0.001 ± 0.000 mg/L to 0.309 ± 0.002 mg/L; Cd (II), 0.067 ± 0.002 mg/L to 0.163 ± 0.002 mg/L; Pb (II), 2.613 ± 0.012 mg/L to 10.712 ± 0.025 mg/L; Ni (II), 0.012 ± 0.020 mg/L to 0.224 ± 0.007 mg/L; Cr (III), 0.002 ± 0.006 mg/L to 0.114 ± 0.002mg/L.